2014
DOI: 10.4049/jimmunol.1400853
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion Abates Porphyromonas gingivalis–Induced Alveolar Bone Resorption in Mice

Abstract: The role of the macrophage in the immunopathology of periodontitis has not been well defined. In this study, we show that intraoral inoculation of mice with Porphyromonas gingivalis resulted in infection, alveolar bone resorption, and a significant increase in F4/80+ macrophages in gingival and submandibular lymph node tissues. Macrophage depletion using clodronate-liposomes resulted in a significant reduction in F4/80+ macrophage infiltration of gingival and submandibular lymph node tissues and significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
144
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 105 publications
(135 reference statements)
13
144
0
1
Order By: Relevance
“…Although the regulation of osteoclastogenesis by macrophages has not previously been reported, macrophages and (pre)osteoclasts can colocalize in the context of inflammatory bone lesion, such as that seen in periodontal disease and arthritis (6,7). While identification of the major macrophage phenotype in human periodontal disease remains elusive (34), we showed that LPS from P. gingivalis, a keystone pathogen in periodontal tissue, can induce M1 macrophages, which suggested that polarization toward the M1 phenotype may occur in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the regulation of osteoclastogenesis by macrophages has not previously been reported, macrophages and (pre)osteoclasts can colocalize in the context of inflammatory bone lesion, such as that seen in periodontal disease and arthritis (6,7). While identification of the major macrophage phenotype in human periodontal disease remains elusive (34), we showed that LPS from P. gingivalis, a keystone pathogen in periodontal tissue, can induce M1 macrophages, which suggested that polarization toward the M1 phenotype may occur in periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…While identification of the major macrophage phenotype in human periodontal disease remains elusive (34), we showed that LPS from P. gingivalis, a keystone pathogen in periodontal tissue, can induce M1 macrophages, which suggested that polarization toward the M1 phenotype may occur in periodontal tissue. Furthermore, it was reported that infiltration of both M1 and M2 macrophages increased in the P. gingivalis-induced mouse periodontitis lesion and that depletion of macrophages using clodronate liposomes prevented the bone resorption induced in the P. gingivalis-infected mice (7). However, since it must be noted that clodronate liposomes can also suppress osteoclastogenesis (35), further investigation may be required to establish the direct impact of either M1 or M2 macrophages on in vivo osteoclastogenesis induced in mice by P. gingivalis infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of NALP3 positive cells was also significantly associated with the level of inflammatory cell infiltration, ASC, caspase-1, IL-1β and IL-18 [172], suggesting that inflammasomes play an important role in production of IL-1 in periapical lesions. In a mouse P. gingivalis -induced periodontitis model, macrophage is an important source of proinflammatory mediators including nitric oxide (NO), IL-1β, IL-6, IL-10, IL-12 p70, eotaxin, G-CSF (granulocyte-colony stimulating factor), GM-CSF, MCP (monocyte chemoattractant protein)-1, MIP-α and -β, and TNF-α [173]. Depletion of macrophage using clodronate liposomes in this disease model resulted in suppression of P. gingivalis -induced immune response such as pathogen-specific IgG (immunoglobulin G) and serum cytokine levels [173].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Periapical mentioning
confidence: 99%
“…Investigating the activation of macrophage phenotypes in response to a periodontal pathogen may provide insights into important host-pathogen interactions. We have previously shown that macrophages in the gingival tissue of mice exhibiting alveolar bone resorption through infection with P. gingivalis expressed high levels of CD86 and lower levels of CD206, suggesting M1 macrophage polarization (27). The aim of this study was to investigate the response P. gingivalis LPS induces in pre-M1-M and pre-M2-M and the subsequent maturation of these macrophages.…”
mentioning
confidence: 99%